Saving Behavior in Latin America: Overview and Policy Issues - Michael Gavin; Ricardo Hausmann; Ernesto Talvi (Inter-American Development Bank, Office of the Chief Economist, 1997)
This paper reviews and contributes to the policy debate on the issue of saving in Latin America, presenting an alternative perspective on the relationship between saving and growth, saving and inflation stabilization and structural reform, and saving and capital flows.
Keywords: 330